Conducta autolesiva no suicida en adolescentes y su relación con factores personales y contextuales - Obando, Diana; Trujillo, Ángela; Prada, Manuel (Revista de Psicopatología y Psicología Clínica, 2019)
Abstract: Non-suicidal self-injury among adolescents and its interaction with personal and contextual factors. Epidemiological studies in mental health indicate an increase in the prevalence of non-suicidal self-injury behaviors in adolescents. However, scarce studies in Latin America explore in depth this problematic behavior. Two studies were conducted using a mixed methodology in order to characterize this phenomenon and to identify associated clinical variables in a group of 1517 adolescents and 43 patients. Additionally, the mediator effect of sensation seeking in the relationship between family attachment and self-injury was assessed. Quantitative results indicate a relationship between self-injury and personal and contextual variables as impulsivity, sensation seeking and family dynamics. Qualitative analysis indicated that self-injury is presented in comorbidity with other complex problematics at the affective, social, academic and familiar levels of the participants. Results relevance is discussed for the clinical context. Resumen: Diferentes estudios epidemiológicos en salud mental indican un aumento en la prevalencia de comportamientos autolesivos en adolescentes. Sin embargo, escasos estudios en Latinoamérica exploran esta problemática en profundidad. Por medio de dos estudios con metodología mixta, el presente trabajo consistió en la caracterización de la autolesión y en la identificación de variables clínicas asociadas en una muestra de 1517 adolescentes y de 43 pacientes. Así mismo, se evaluó el efecto mediador de la búsqueda de sensaciones en la relación entre el apego familiar y la autolesión. Los resultados cuantitativos indican una relación entre la autolesión y factores personales y contextuales, tales como la impulsividad, la búsqueda de sensaciones y las dinámicas familiares. El análisis cualitativo indica que la autolesión se presenta en comorbilidad con otras problemáticas complejas en los niveles afectivo, social, académico y familiar de los pacientes. Se discute la relevancia de los resultados a nivel clínico.